Identification of elongation factor‐2 as a novel regulator of mitochondrial fission. Issue 3 (10th May 2022) - Kim, Jinhwan; Li, Yanfeng; Cheng, Yan; Ren, Xingcong; Zhang, Yi; Ji, Cheng; Zhu, Hua; Takahashi, Yoshinori; Xiong, Xingdong; Gu, Lixiang; Ngule, Chrispus; Xiong, Xiaofang; et al.
Abstract: Mitochondria continuously undergo morphologically dynamic processes of fusion and fission to maintain their size, shape, amount, and function; yet the precise molecular mechanisms by which mitochondrial dynamics is regulated remain to be fully elucidated. Here, we report a previous unappreciated but critical role of eukaryotic elongation factor 2 (eEF2) in regulating mitochondrial fission. eEF2, a G‐protein superfamily member encoded by EEF2 gene in humans, has long been appreciated as a promoter of the GTP‐dependent translocation of the ribosome during protein synthesis. We found unexpectedly in several types of cells that eEF2 was not only present in the cytosol but also in the mitochondria. Furthermore, we showed that mitochondrial length was significantly increased when the cells were subjected to silencing of eEF2 expression, suggesting a promotive role for eEF2 in the mitochondrial fission. Inversely, overexpression of eEF2 decreased mitochondrial length, suggesting an increase of mitochondrial fission. Inhibition of mitochondrial fission caused by eEF2 depletion was accompanied by alterations of cellular metabolism, as evidenced by a reduction of oxygen consumption and an increase of oxidative stress in the mitochondria. We further demonstrated that eEF2 and Drp1, a key driver of mitochondrial fission, colocalized at the mitochondria, as evidenced by microscopic observation, coimmunoprecipitation, and GST pulldown assay. Deletion of the GTP‐binding motif of eEF2 decreased its association with Drp1 and abrogated its effect on mitochondria fission. Moreover, we showed that wild‐type eEF2 stimulated GTPase activity of Drp1, whereas deletion of the GTP‐binding site of eEF2 diminished its stimulatory effect on GTPase activity. This work not only reveals a previously unrecognized function of eEF2 (i.e., promoting mitochondrial fission), but also uncovers the interaction of eEF2 with Drp1 as a novel regulatory mechanism of the mitochondrial dynamics. Therefore, eEF2 warrants further exploration for its potential as a therapeutic target for the mitochondria‐related diseases. Key Points: We demonstrate that eEF‐2 localizes in the mitochondria, in addition to its presence in the cytosol. This study identifies eEF‐2 as a novel regulator of mitochondrial fission. This work uncovers the interaction of eEF‐2 with Drp1 and its effect on GTPase activity as a new mechanism that regulates mitochondrial dynamics. Abstract : Here, we report a previous unappreciated but critical role of eukaryotic elongation factor 2 (eEF2) in regulating mitochondrial fission. eEF2, a G‐protein superfamily member encoded by EEF2 gene in humans, has long been appreciated as a promoter of the GTP‐dependent translocation of the ribosome during protein synthesis. This work not only reveals a previously unrecognized function of eEF2 (i.e., promoting mitochondrial fission), but also uncovers the interaction of eEF2 with Drp1 as a novel regulatory mechanism of the mitochondrial dynamics.